Effect of khat, its constituents and restraint stress on free radical metabolism of rats - M. Al-Qirim, Tariq; Shahwan, Moyad; R. Zaidi, Kashif; Ahmed, Qamar Uddin; Banu, Naheed (Elsevier Ireland Ltd, 2002)

(untitled)
The leaves of khat (Catha edulis ) are found to have stimulating and pleasurable effect and are chewed habitually by people of East Africa and Arabian Peninsula. Due to various toxic and psychostimulative effect of khat the present study was undertaken to evaluate the effect of intragastric khat alone or its major constituents flavonoids/alkaloids administration and before and after 4 h of immobilization stress in terms of alteration of free radical scavenging/metabolizing enzymes, uric acid and glucose in rats. Oral khat, alkaloid administration or 4 h restraint stress resulted in the decrease of the circulating levels of superoxide dismutase, catalase, glutathione-S-transferase and glucose with enhanced uric acid concentrations as compared with control rats. Oral treatment with flavonoid fraction of khat was found to enhance the activities of GST and catalase but showed no effect on SOD while the level of glucose was decreased and uric acid increased. The levels of these biochemical parameters were more altered in post stress khat/ alkaloid treated rats than pre stress khat/alkaloid treated rats. The alteration in the levels of SOD, GST, catalase and uric acid in the pre stress khat treated rats were comparable with that of khat alone, except the level of glucose which was further decreased in pre stress khat treated rats. The flavonoid fraction of khat reduced the stress induced oxidative stress in terms of above mentioned biochemical parameters. The present study suggests that khat alone or khat/alkaloid consumption preceding stress may significantly decrease the levels of free radical metabolizing/scavenging enzymes and glucose leading to enhanced free radical concentration and toxicity of khat, which could be due to its alkaloid fraction as flavonoids were found to show antioxidant properties for oxidative stress generated during restraint stress.